Assessment of human exposure doses received by activation of medical linear accelerator components. (31st August 2017) - Lee, D.-Y.; Kim, J.-H.; Park, E.-T.
Abstract: This study analyzes the radiation exposure dose that an operator can receive from radioactive components during maintenance or repair of a linear accelerator. This study further aims to evaluate radiological safety. Simulations are performed on 10 MV and 15 MV photon beams, which are the most frequently used high-energy beams in clinics. The simulation analyzes components in order of activity and the human exposure dose based on the amount of neutrons received. As a result, the neutron dose, radiation dose, and human exposure dose are ranked in order of target, primary collimator, flattening filter, multi-leaf collimator, and secondary collimator, where the minimum dose is 9.34E-07 mSv/h and the maximum is 1.71E-02 mSv/h. When applying the general dose limit (radiation worker 20 mSv/year, pubic 1 mSv/year) in accordance with the Nuclear Safety Act, all components of a linear accelerator are evaluated as below the threshold value. Therefore, the results suggest that there is no serious safety issue for operators in maintaining and repairing a linear accelerator. Nevertheless, if an operator recognizes an exposure from the components of a linear accelerator during operation and considers the operating time and shielding against external exposure, exposure of the operator is expected to be minimized.